2015
DOI: 10.1017/s0047279415000288
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Cost or Culture? Obstacles to Childcare Services for Low-Income Families

Abstract: Recent research has highlighted the existence of a social bias in the extent to which children have access to childcare. In general, children living in higher income households are more likely to be cared for in childcare centres. While the existence of a social bias in access to childcare services has been clearly demonstrated, we currently lack a clear explanation as to why this is the case. This paper uses a unique dataset based on survey data collected specifically to study patterns of childcare use in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 12 publications
6
61
0
2
Order By: Relevance
“…Other research endeavours focusing on single countries found similar patterns, for instance in the USA (Fuller and Xiaoyan 1996;Meyers et al 2004;Greenberg 2011) and in several European countries (e.g. Abrassart and Bonoli 2015;Krapf 2014;Vandenbroeck et al 2014;Van Lancker and Ghysels 2012;Del Boca and Pasqua 2005;Spieß et al 2003). Only Denmark, Iceland and to a lesser extent Sweden report equity in childcare use amongst young children from different socio-economic backgrounds (Meagher and Szebehely 2012).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Other research endeavours focusing on single countries found similar patterns, for instance in the USA (Fuller and Xiaoyan 1996;Meyers et al 2004;Greenberg 2011) and in several European countries (e.g. Abrassart and Bonoli 2015;Krapf 2014;Vandenbroeck et al 2014;Van Lancker and Ghysels 2012;Del Boca and Pasqua 2005;Spieß et al 2003). Only Denmark, Iceland and to a lesser extent Sweden report equity in childcare use amongst young children from different socio-economic backgrounds (Meagher and Szebehely 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Earlier studies focused on the impact of costs on the labour supply of women and found that expensive childcare services decrease the labour supply of women with low earnings potential, such as women with lower levels of education (Blau and Robins ; Connelly ). Recent studies, however, tend to focus more on the availability of places in childcare in determining enrolment decisions (Wrohlich ), although some scholars argue that the impact of childcare costs, however, should not be underestimated (Abrassart and Bonoli ). Single‐country studies found that the social differential in childcare use within countries is most strongly related to structural factors, such as shortage in the number of available childcare slots, the availability and generosity of parental leave schemes, and employment opportunities in the labour market (Del Boca and Vuri ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of public spending on reducing inequality is only indirect, mediated via higher overall levels of enrolment. Despite increasing levels of public childcare spending, income inequality in enrolment can be highly persistent (Van Lancker 2013Abrassart and Bonoli 2015;Van Lancker and Ghysels 2016). The persistence of inequality in childcare enrolment has been found to hinge on the dimensions of universalism, and the state-market mix in childcare provision (Van Lancker and Ghysels 2016).…”
Section: The Conditioning Impact Of Inequality In Childcare Provisionmentioning
confidence: 99%
“…With regard to the first dimension, in the presence of an often insufficient supply of childcare, having established access to childcare as a legal right bolsters parents' position in their attempt to use these services and implies an incentive for the government to expand provision. In addition, levels of private fees need to be sufficiently low to ensure that services are affordable for parents (Abrassart and Bonoli 2015). The second dimension concerns the difference between state-and market-based provisions.…”
Section: The Conditioning Impact Of Inequality In Childcare Provisionmentioning
confidence: 99%
“…So können verschiedene empirische Studien zwar zeigen, dass Familien aus mittleren und oberen sozialen Schichten häufiger von sozialen Dienstleistungen wie Kinderbetreuung Gebrauch machen und profitieren(Ghysels/Van Lancker 2011; OECD 2011;Van Lancker 2013), dies kann aber von vielen Faktoren abhängen, wie bspw. der Höhe und Ausgestaltung der Kita-Gebühren(Abrassart/Bonoli 2015). Davon die Annahme abzuleiten, sozial schlechter gestellte Familien würden Maßnahmen zur Vereinbarkeit von Familie und Beruf weniger befürworten oder brauchen, scheint allerdings nicht notwendigerweise gerechtfertigt.…”
unclassified